WALLS, Laura Dassow (2019). Henry David Thoreau: Una vida. Madrid: Cátedra. 624 pp. - Clares, Diego (Daimon Revista Internacional de Filosofia, 2021)
RESEÑA de: WALLS, Laura Dassow (2019). Henry David Thoreau: Una vida. Madrid: Cátedra. 624 pp.